2010
DOI: 10.1038/nsmb.1720
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant alternative splicing and extracellular matrix gene expression in mouse models of myotonic dystrophy

Abstract: Myotonic dystrophy (DM1) is associated with expression of expanded CTG DNA repeats as RNA (CUGexp RNA). To test whether CUGexp RNA creates a global splicing defect, we compared skeletal muscle of two mouse DM1 models, one expressing a CTGexp transgene, and another homozygous for a defective Mbnl1 gene. Strong correlation in splicing changes for ~100 new Mbnl1-regulated exons indicates loss of Mbnl1 explains >80% of the splicing pathology due to CUGexp RNA. In contrast, only about half of mRNA level changes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
420
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(457 citation statements)
references
References 64 publications
33
420
0
Order By: Relevance
“…RNAs harboring a long stretch of repeats are thought to fold into stable structures and sequester RNA binding proteins, which, in turn, sets off a molecular cascade leading to neurodegeneration (7). In myotonic dystrophy, sequestration and functional disruption of the muscleblind-like family of RNA binding proteins are associated with specific splicing and expression changes in affected tissues (5,(8)(9)(10)(11)(12).Sequestration of one or more RNA binding proteins into pathological RNA foci has also been proposed in ALS/FTD linked to C9orf72 expansion (1, 13-16). It is anticipated, but has not been demonstrated, that sequestration of RNA binding proteins into expanded GGGGCC RNA foci may lead to major RNA processing alterations as in myotonic dystrophy.…”
mentioning
confidence: 99%
“…RNAs harboring a long stretch of repeats are thought to fold into stable structures and sequester RNA binding proteins, which, in turn, sets off a molecular cascade leading to neurodegeneration (7). In myotonic dystrophy, sequestration and functional disruption of the muscleblind-like family of RNA binding proteins are associated with specific splicing and expression changes in affected tissues (5,(8)(9)(10)(11)(12).Sequestration of one or more RNA binding proteins into pathological RNA foci has also been proposed in ALS/FTD linked to C9orf72 expansion (1, 13-16). It is anticipated, but has not been demonstrated, that sequestration of RNA binding proteins into expanded GGGGCC RNA foci may lead to major RNA processing alterations as in myotonic dystrophy.…”
mentioning
confidence: 99%
“…38 Several studies have addressed the effects of loss of MBNL1 at the molecular and the phenotypical level. 18,23,32,39 Du et al 32 compared a mouse model expressing a (CUG) n expansion with a mbnl1 knockout mouse. RNA expression was grossly disturbed with mainly splicing defects.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 480% of these effects were due to loss of MBNL1 function. 32 Jog et al 30 demonstrated a gene dosage effect: the splicing activity of MBNL1 is dependent on the number of active gene copies. The splicing pattern shifted from the adult to the fetal pattern concomitant with the rate of loss in MBNL1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is severely misregulated in DM1 patients and in HSA LR mice (11,12). We analyzed alternative splicing patterns in transcripts of two direct Mbnl1 targets: the muscle sarcoplasmic/endoplasmic reticulum Ca 2þ ATPase (Serca1) and fast skeletal muscle troponin T (Tnnt3).…”
Section: Abp1 Reversed Missplicing and Muscle Histopathology In A Dm1mentioning
confidence: 99%
“…CTGrepeat expression in mice caused misregulation of at least 156 alternative splicing events. Of these, 128 also occurred in Mbnl1 knockout animals (9)(10)(11)(12). The splicing factor CUG-binding protein 1 (CUGBP1) is another key component in the development of DM1 phenotypes.…”
mentioning
confidence: 99%